STUDI KASUS TENTANG SISWI YANG MEMILIKI KEPRIBADIAN MASKULIN DI KELAS XI SMA NEGERI 9 PONTIANAK TAHUN 2016 - Rismawati, Rismawati; Yuline, Yuline; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract Personality is the character of a person who is seen through his behavior as a whole so that it describes a specific and consistent personal identity. Masculine is the inherent nature of men describing the condition of men who tend to be free, aggressive, and emotional. Students who have masculine personalities are female students who have the nature and appearance of men who are not necessarily owned by women. General research problem: